Pengembangan Media Pembelajaran QuizWhizzer dan Kinemaster untuk Meningkatkan Motivasi Belajar Siswa di Sekolah Dasar - Sofyan Iskandar; Primanita Sholihah Rosmana; Aflahatul Fazriyah; Agung Febriyano; Alya Amrina Rosyada (Departement of Mathematics Education, 2023)
This study aims to develop digital learning media using the video editor application kinemaster and Quizwhizzer as an evaluation to increase students' learning motivation in learning IPAS. Research The development of this learning media uses qualitative research methods. The research was conducted by observation to determine the success of student learning, researchers conducted pretest and posttest to students. From the observation results, it can be seen that learning using the video editor application kinemaster and quizwhizzer can increase student learning motivation, this can be seen when learning takes place, many students are active.